2013
DOI: 10.1063/1.4789981
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and length scale dependence of solvophobic solvation in a single-site water-like liquid

Abstract: The temperature and length scale dependence of solvation properties of spherical hard solvophobic solutes is investigated in the Jagla liquid, a simple liquid that consists of particles interacting via a spherically symmetric potential combining a hard core repulsion and a longer ranged soft core interaction, yet exhibits water-like anomalies. The results are compared with equivalent calculations for a model of a typical atomic liquid, the Lennard-Jones potential, and with predictions for hydrophobic solvation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
4
10
0
Order By: Relevance
“…The growth of the contact correlations appears to approach an asymptotic plateau with increasing radius, consistent with the expected contact density for a flat interface of f3P/ p = 7.75 (Table I) as dictated by the wall theorem [40]. Compared against the spherical solute, the cylinder's contact correlation (13) and (18)], the fit of spherical RSPT to the spherical cavity simulations [11,14], and predictions of the cylindrical contact correlation using the end cap approximation [Eq. (12)].…”
Section: A Hard-sphere Solventsupporting
confidence: 66%
See 1 more Smart Citation
“…The growth of the contact correlations appears to approach an asymptotic plateau with increasing radius, consistent with the expected contact density for a flat interface of f3P/ p = 7.75 (Table I) as dictated by the wall theorem [40]. Compared against the spherical solute, the cylinder's contact correlation (13) and (18)], the fit of spherical RSPT to the spherical cavity simulations [11,14], and predictions of the cylindrical contact correlation using the end cap approximation [Eq. (12)].…”
Section: A Hard-sphere Solventsupporting
confidence: 66%
“…Following Stillinger, Ashbaugh and Pratt developed a revised SPT (RSPT) in which multibody solvent correlations determined from simulations are used to provide an improved description of molecular-scale solvation. Revised SPT has successfully been applied to quantitatively evaluate the solvation free energy of spherical solutes in water [12] and waterlike [13] solvents as well as Lennard-Jones [11,14] and organic solvents [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that many structural, thermodynamic, and dynamic properties of water can be reproduced using soft-core spherically symmetrical potentials [7][8][9][10] although certain tradeoffs are necessary due to the transferability issue. 11,12 Angular dependence of hydrogen bonding is necessarily forgone and compensated for with two characteristic lengths that these models must have.…”
Section: Introductionmentioning
confidence: 99%
“…The same behavior is encountered when using Jagla potential or cavity equation of state (C-EoS) for water. 60 A different solvation mechanism for small and large particles is proposed as an explanation for this behavior.…”
Section: A Temperature Dependencementioning
confidence: 99%